Influence of salt substitute containing KCl, L-histidine and L-lysine on the secondary structure and gel properties of myosin - Yawei Zhang; Muneer Ahmed Jamali; Zengqi Peng (CyTA - Journal of Food, 2019)
The effect of a salt substitute (SS) containing L-lysine (Lys) and L-histidine (His) on secondary structure and gel properties of myosin from grass carp was examined. The results indicated that the α-helix content of myosin treated with SS was 29.00%, 29.03% and 35.93% more than that with NaCl at 0.4, 0.6 and 0.8 mol/L (P < 0.05), respectively, suggesting that some fractions of the β-sheet, β-turn and random coil were transformed into α-helix. A similar pattern of storage modulus (G’) was found between NaCl and SS treatments, and the G’ of SS treatments at the end of gelation completion was higher than that of NaCl treatments. The salt substitute improved the gel strength and hardness of myosin at 0.4, 0.6 and 0.8 mol/L. The results indicated that the changes in secondary structure and gel properties of myosin may be mainly due to the L-lys and/or L-his in salt substitute.